Digital transformation and corporate governance: A systematic literature review. - Bidin, Samsiah; Ahmad , Afida; Saad , Abidah (International Journal of Accounting, Finance and Business, 2025)
Digital transformation has emerged as a transformative force in higher education institutions, driven by advancements in the Fourth Industrial Revolution and further accelerated by the global disruptions caused by the COVID-19 pandemic. This systematic literature review investigates the comprehensive impact of digital transformation on higher education, particularly in relation to institutional governance, sustainability practices, risk management, and academic performance. The study addresses a critical gap in understanding how digital technologies are reshaping administrative functions, stakeholder engagement, and decision-making frameworks within higher education. Using the PRISMA methodology and an advanced search strategy applied to the Scopus database; an initial pool of 265 documents was identified. Following a rigorous selection process involving screening, eligibility assessment, and quality appraisal, a final sample of 31 peer-reviewed journal articles and conference papers published between 2020 and 2025 was chosen for in-depth analysis. These studies were thematically synthesized into three dominant themes: governance mechanisms and institutional reform, sustainability and environmental, social, and governance innovation, and digital risk management alongside performance enhancement. The findings demonstrate that digital transformation improves transparency, supports responsive and inclusive governance structures, and enables evidence-based policy development. It also contributes to sustainability through digitalised operations, such as paperless systems and remote learning, while enhancing institutional resilience and operational efficiency. Despite these advancements, higher education institutions continue to face challenges including digital inequality, cybersecurity vulnerabilities, and a lack of digital leadership capacity. Overall, the review highlights digital transformation as a strategic enabler of innovation and resilience in higher education. It provides valuable insights for policymakers, academic leaders, and institutional planners aiming to optimise digital initiatives to support long-term sustainability, adaptability, and performance improvement across the higher education sector.